Peningkatan Pemahaman Mengenai Kebijakan Kesehatan di Wilayah Perbatasan Indonesia Bersama Mahasiswa Universitas Kristen Artha Wacana Kupang - Posma Sariguna Johnson Kennedy; Ayub U.I. Meko; Tobing, Suzanna Josephine L.; Toruan, Rutman L. (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
This activity aims to increase understanding of health policy issues in Indonesia's border areas. The activity method carried out is conducting a discussion (Forum Group Discussion) with lecturers and students at the Universitas Kristen Artha Wacana Kupang. While the writing method used is a descriptive approach. It is necessary to increase the development of health and supporting infrastructure in border areas. Socialisation and improvement of health insurance services from the government also need to be carried out, as well as increasing the competence of health workers or all human resources in the health sector.